2000
DOI: 10.1523/jneurosci.20-03-00969.2000
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptors Trigger Homosynaptic Protein Synthesis to Prolong Long-Term Potentiation

Abstract: We investigated the mechanisms by which previous "priming" activation of group I metabotropic glutamate receptors (mGluRs) facilitates the persistence of long-term potentiation (LTP) in area CA1 of rat hippocampal slices. Priming of LTP was elicited by either pharmacological or synaptic activation of mGluRs before a weak tetanic stimulus that normally produced only a rapidly decaying phase of LTP that did not involve protein synthesis or mGluRs. Pharmacological priming of LTP persistence by a selective group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(196 citation statements)
references
References 55 publications
11
171
0
1
Order By: Relevance
“…Interestingly, the newly synthesized proteins promote LTP stability in an input-specific manner. The homosynaptic restriction of the function of newly synthesized proteins is consistent with the idea that at least some of the new proteins that are essential for LTP expression are synthesized at the activated synapses (Raymond et al 2000). Huber et al (2000) recently reported that LTD induced by mGluR stimulation, in CA1 stratum radiatum severed from cell body layers, could be blocked by translational inhibitors, indicating a requirement for local protein synthesis for the expression of this form of LTD.…”
Section: Local Protein Synthesis During Synaptic Plasticity and Synapsupporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, the newly synthesized proteins promote LTP stability in an input-specific manner. The homosynaptic restriction of the function of newly synthesized proteins is consistent with the idea that at least some of the new proteins that are essential for LTP expression are synthesized at the activated synapses (Raymond et al 2000). Huber et al (2000) recently reported that LTD induced by mGluR stimulation, in CA1 stratum radiatum severed from cell body layers, could be blocked by translational inhibitors, indicating a requirement for local protein synthesis for the expression of this form of LTD.…”
Section: Local Protein Synthesis During Synaptic Plasticity and Synapsupporting
confidence: 79%
“…However, inhibition of protein synthesis diminished only the increase in MAP2, not αCaMKII protein in the dendritic domains (Steward & Halpain 1999), indicating a protein-synthesis-independent mechanism for the observed increase in αCaMKII protein in the activated dendrites. Signals that are mediated by NMDA mGluRs are probably involved in triggering regulated local protein synthesis after synaptic activation (Raymond et al 2000;Scheetz et al 2000). Protein synthesis regulated by synaptic activity has been reported in the sensory neuron processes of Aplysia, and local application of protein synthesis inhibitors at a particular synapse can block long-term facilitation (LTF) at this synapse, but not at the other synapses on the same cells (Martin et al 1997).…”
Section: Regulation Of Dendritic Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Application of DHPG onto either hippocampal or cerebellar slices induces a long-term depression that requires dendritic protein synthesis but not transcription (35,40,41). Furthermore, DHPG application has also been reported to enhance both hippocampal long-term potentiation and the epileptogenic effects of picrotoxin in a protein synthesisdependent fashion (42,43). The requirements for protein synthesis in these various paradigms are very brief (10-15 min), suggesting that a ''pulse'' of translation is rapidly activated and then turned off (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…A case in point is a form of LTD triggered by mGluR5 activation in the hippocampus, which requires mRNA translation but not transcription (Huber et al, 2000). The same can be said of mGluR-dependent epileptogenesis (Merlin et al, 1998), dendritic spine elongation (Vanderklish and Edelman, 2002), LTP priming (Raymond et al, 2000), and LTP reversal (Zho et al, 2002) in the hippocampus.…”
Section: Metabotropic Glutamate Receptormentioning
confidence: 99%